Probability Evaluation Models of Product Disassembly Cost Subject to Random Removal Time and Different Removal Labor Cost - Tian, Guangdong; Zhou, MengChu; Chu, Jiangwei; Liu, Yumei (IEEE transactions on automation science and engineering, 2012)
Disassembly is a systematic method to separate an end-of-life product into its constituent parts and components. However, the disassembly process of products can experience great uncertainty due to a variety of unpredictable factors. To deal with such uncertainty, this work proposes a novel probability analysis method of disassembly cost with random removal time and different removal labor cost. According to different constraints and actual execution of disassembly, it presents typical probability evaluation models of disassembly cost. Moreover, a solution algorithm based on stochastic simulation is used to solve the proposed probability models. Some numerical examples are given to illustrate the proposed concepts and the effectiveness of the proposed algorithm.